Dementia Meeting Centres: People Affected by Dementia Take the Lead - Graham Galloway; Shirley Evans; Ronald Coleman (International Journal of Integrated Care, 2023)
Meeting Centres (MC) are a flexible, hyper-local model for dementia post-diagnostic support, which create engaging, enabling, and empowering spaces for families affected by dementia. MCs offer ongoing warm and friendly expert assistance, including peer support, for people and families affected by dementia. The model originated in the Netherlands, led by Professor Rose-Marie Dröes at the Amsterdam University Medical Centers. Meeting Centres UK was established in 2018 and led by the Association for Dementia Studies (ADS), University of Worcester. In 2019 Kirrie Connections set up the first Scottish MC. Prior to the COVID-19 pandemic, there were 13 MCs in the UK. Despite the pandemic, there are now 32 funded MCs in England and Wales and 14 in Scotland with the likelihood of another 10 being funded before the end of 2023. Significant national and regional developments have taken place over the last three years. This has been driven by different policy decisions and funding opportunities across the three nations and has involved a variety of partnership working between academic, local authority, third sector, government and lived experience partners. The Scottish Government is supporting the development of a national MC network because of the recognition that capacity can be built, best practice shared, and communities empowered. In addition, the involvement of people affected by dementia is of paramount importance. In Scotland, this is being driven forward with a strategy board made up of a third people living with dementia, a third family carers and a third dementia professionals. This is being replicated in the new UK National MC Consortium. In the presentation, the different contexts and approaches to MCs will be described and compared. The audience will gain an understanding of the flexibility of the MC model in meeting the needs of people affected by dementia in different communities; the MC grassroots community development approach; and the impact of the involvement of people affected by dementia in the meaningful ongoing coproduction of MCs. Brooker, D., Evans, S., Dröes, R. M., (2016), Framing outcomes of post-diagnostic psychosocial interventions in dementia: The Adaptation-Coping Model and Adjusting to Change. Working with Older People. Vol 21: Issue 1 Evans, S., Bray, J. and Brooker, D. (2021), ""How Meeting Centres continue to support people affected by dementia: report on UK COVID-19 impact"", Working with Older People, Vol. 25 No. 4, pp. 283-293. https://doi.org/10.1108/WWOP-12-2020-0060 Evans, S., Bray, J., Brooker, D. and Stephens, N. (2022), ""The essential features of Meeting Centres: development of the UK criteria for community support for people affected by dementia"", Working with Older People, Vol. ahead-of-print No. ahead-of-print. https://doi.org/10.1108/WWOP-03-2022-0009